A comparative study of three dietary methods in evaluating food consumption among 4-6 year old children in Nibaliw, Mangaldan, Pangasinan - Vargas, Marina Barrozo
Pre-school children are the emphasis of current nutrition and health programs because they are vulnerable to malnutrition. Thus, appropriate dietary assessment method is necessary in order to obtain qualit data that will serve as basis in creating intervention programs for this age group. This study compared three dietary methods, namely; weighed food record, repeated food recalls and quantitative food frequency in terms of estimation of average nutrient intake, variability, accuracy and administrative problems. Food intakes of pre-school children aged 4-6 year old were evaluated using the three dietar methods.A total of 80 preschoolers were included in the study. One-day weighed food record was collected by the principal investigator. The three-day food recall and the quantitative food frequency for past seven days were collected by the two trained local researchers through personal interview. Dietary data obtained were analyzed for energy, protein, iron and vitamin A.This study showed that (1) the one-day food weighing (FW), three-day food recall (RFR) and quantitative food frequency (QFF) for past seven days had comparable estimates for mean protein, iron and vitamin A intakes; (2) the QFF estimates for energy and the three nutrients had the highest percent adequacy than the two methods; (3) Pearson's correlation coefficient and percentage agreement showed a close similarity of estimates between FW and RFR, while the comparisons between QFF and RFR, and the FW and QFF had large differences in their estimates; (4) the 24-hour FR estimates were seen to be more variable compared with that of FW, and the RFR estimates were more viable compared with that of QFF; (5) the 24-hour FR can give accurate estimates for energy, and the three nutrients as that of FW; and (6) the QFF method was the easiest to administer and required less time and low respondent's burden.This study conclude that (1) the three dietary methods can be used interchangeably when estimating average intakes for protein, iron and vitamin A; (2) the 24-hour FR and FW can be used interchangeably when assessing group or individual food intakes; and (3) in terms of ease of administration, time element, and respondent's burden, the QFF method was found to be the most feasible to use when assessing food intakes of the subjects.Similar to other dietary investigations, this study confirmed that there is no ideal or standard method of collecting dietary information. The method of choice will depend on the purpose and objectives of the study.
Thesis (Master of Science in Public Health, Nutrition)--University of the Philippines Manila.
Keywords: Nutrition -- Requirements; Children -- Nutrition; Dietary methods